Study the Improvement of Higher Education in Human Resources: Enhancing Education System in the Chhatarpur Region of Madhya Pradesh (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Human resource management is concerned with enhancing an organization's HR division.Human resource development is made up of the two main parts, human resources, and development(HRD). Human resources (HR) are an organization's most important asset since they include not just thecollective wisdom but also the unique qualities and benefits of each individual employee. The studyconcludes that the education system in the Chhatarpur region of the state Madhya Pradesh needs achange in order to keep up with evolving technologies or develop into a well-managed education systemin which educational institutions take on the responsibility of fostering the development of students'abilities and values and position themselves as a knowledge base in order to foster the emergence of asociety that is founded on the implementation of that knowledge.